Critical literature review and pooled analysis of diagnostic accuracy of Ortho VITROS SARS-CoV-2 antigen test for diagnosing acute SARS-CoV-2 infections: Pooled analysis of VITROS SARS-CoV-2 antigen test - Lippi, Giuseppe; Nocini, Riccardo; Henry, Brandon Michael (Journal of Medical Biochemistry, 2022)
Background: The present study is aimed at reviewing and meta-analyzing the currently published data on the diagnostic accuracy of Ortho VITROS SARS-CoV-2 antigen test for diagnosing acute SARS-CoV-2 infections. Methods: An electronic search was conducted in Scopus and Medline with the keywords “VITROS” AND “antigen” AND “COVID-19” OR “SARS-CoV-2” AND “immunoassay” within the search fields “TITLE” AND “ABSTRACT” AND “KEYWORDS”, without no date (i.e., up to January 23, 2022) or language restrictions, aimed at detecting documents reporting the diagnostic accuracy of this SARS-CoV-2 immunoassay compared with reference molecular diagnostic methods. Results: Overall, 5 studies (n=2734 samples) were finally included in our pooled analysis, four of which also provided diagnostic sensitivity in oro- and nasopharyngeal samples with high viral load. The pooled cumulative diagnostic sensitivity and specificity were 0.82 (95%CI, 0.78-0.86) and 1.00 (95%CI, 1.00-1.00), respectively, whilst the area under the curve was 0.995 (95%CI, 0.993-0.997), the cumulative agreement 97.2% (95%CI, 96.5-97.8%), with 0.89 (95%CI, 0.86-0.91) kappa statistics, thus reflecting an almost perfect concordance with reference molecular biology techniques. The pooled diagnostic sensitivity in samples with high viral load was as high as 0.98 (95%CI, 0.96-0.99). Conclusions: These results confirm that the automated and high-throughput Ortho VITROS SARS-CoV-2 antigen test may represent a valuable surrogate of molecular testing for diagnosing acute SARS-CoV-2 infections, especially in subjects with high viral load.